Immigrant Naturalization in the Context of Institutional Diversity: Policy Matters, but to Whom?. (12th June 2013) - Vink, Maarten Peter; Prokic‐Breuer, Tijana; Dronkers, Jaap
Abstract: Why do some immigrants naturalize and others not? While much of the literature emphasizes the importance of country of origin features and individual characteristics, there is surprisingly little systematic research on the relation between citizenship policies in destination countries and citizenship take‐up among immigrants. Most research in this field draws on data from single country cases and has limited comparative scope. In this paper we analyze citizenship take‐up among first generation immigrants in 16 European countries. We apply an explicit cross‐national perspective and argue that immigrant naturalization in Europe is determined not only by country of origin features and individual characteristics, but also by the opportunity structure set by the citizenship laws in the countries of origin and destination. We show that more accessible citizenship policies matter little for immigrants from highly developed countries, particularly those with fewer years of residence, but matter significantly for immigrants from less developed countries. As the composition of immigrant populations and citizenship policies across Europe vary significantly, this comparative design is ideally suited to testing the relative importance of factors related to country of origin, individual background and legal opportunity structure.